DEVELOPMENT OF WEB GAME LEARNING MATERIALS FOR PRIMARY SCHOOL STUDENTS - Wahyudi Wahyudi; Marisa Ambarwati; Endang Indarini (IKIP Siliwangi and I-MES, 2019)
The purpose of this study is to develop a web-based learning game media to improve problem-solving skills in two-dimensional figure. Research method with R & D use the ASSURE development model consisting of 6 steps, that is 1) analyze learners, 2) state objectives, 3) select method, media, and materials, 4) utilize media and materials, 5) require learner participation, 6) evaluated and revise. The validity of the product is assessed by the experts with the expert validation sheets. The practicality of the product was tested by a limited trial of 10 students followed by interviews to see student responses. The Product effectiveness was seen from one class trial with one group pretest-posttest design and the results were analyzed using the Paired-Samples T-Test. The results of this study are in the form of web-based game learning media to improve problem-solving skills in flat-build material. The Learning media is proved valid based on the expert media, material, and learning tests. Learning media was also proved practical based on the results of interviews by 10 students. Learning media is proved effective based on the Paired Samples T-Test which was taken from the results of the pretest and post test